2007
DOI: 10.1359/jbmr.070611
|View full text |Cite
|
Sign up to set email alerts
|

Maspin Is Involved in Bone Matrix Maturation by Enhancing the Accumulation of Latent TGF-β

Abstract: Maspin, a serine protease inhibitor, is expressed by formative osteoblasts. The repression of maspin expression in osteoblastic cells decreased the level of latent TGF-␤ in the extracellular matrix, whereas the overexpression of maspin increased latent TGF-␤. These findings suggest that maspin plays an important role in bone matrix formation, particularly in the accumulation of latent TGF-␤.Introduction: Maspin is a serine protease inhibitor that exhibits tumor suppressive and anti-angiogenic activities. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…OCN is secreted mostly in mature osteoblasts during the stage of matrix calcification (19). Consistent with previous reports (10,20), dynamic and well-regulated mRNA expression patterns of these marker genes were observed depending on the differentiation stage of non-irradiated osteoblasts (data not shown). Our results also strongly support that the mRNA expression patterns of these bone-specific markers were affected differently according to the quantity of irradiation and the testing times examined (5).…”
Section: Discussionsupporting
confidence: 91%
“…OCN is secreted mostly in mature osteoblasts during the stage of matrix calcification (19). Consistent with previous reports (10,20), dynamic and well-regulated mRNA expression patterns of these marker genes were observed depending on the differentiation stage of non-irradiated osteoblasts (data not shown). Our results also strongly support that the mRNA expression patterns of these bone-specific markers were affected differently according to the quantity of irradiation and the testing times examined (5).…”
Section: Discussionsupporting
confidence: 91%
“…Since, in bone, maspin was reported to be actively expressed in osteoblasts located in site of active bone formation and remodelling, and to act as a TGFβ modulator [58], its over expression in ML bone cells can cause a disequilibrium between the active and latent form of TGFβ, thus playing a role in bone matrix formation.…”
Section: Discussionmentioning
confidence: 99%
“…The cell morphology of ameloblasts and odontoblasts was bizarre, and the alignment of these cells disorganized. It has been recently reported that maspin possesses an activity to enhance the ECM maturation through regulating the accumulation of growth factors (Tokuyama et al 2007). Judging from this report, our phenomena may suggest that the suppression of maspin might result in an inhibition of production and/or maturation of dental matrices.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses tumor suppressive and anti-angiogenic activities (Shi et al 2001;Zhang et al 2000), which are thought to be mediated by an inhibitory eVect of maspin on two plasminogen activators: uPA and tissue type plasminogen activator (tPA) (Biliran and Sheng 2001;Sheng et al 1998). Meanwhile, we previously reported that maspin expressed by active osteoblasts plays an important role in bone matrix maturation by promoting the accumulation of latent TGF-in ECM (Tokuyama et al 2007). This fact reveals that maspin is one of most important molecules facilitating the eVective accumulation of growth factors and matrix proteins in extracellular matrices in tooth development as well as bone formation.…”
Section: Introductionmentioning
confidence: 99%